InvestKL bullish on investors' sentiment - New Straits Times, (2012)
KUALA LUMPUR: InvestKL Corp, a special agency set up to attract more multinational companies (MNCs)to invest in Kuala Lumpur and the Klang Valley, is bullish on investors' sentiment despite the uncertain economic outlook.